2021
DOI: 10.1002/ab.21997
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive interactions and consistency of dominance hierarchies of the native and nonnative cichlid fishes of the Balsas basin

Abstract: Dominance hierarchies are generally established based on the levels of aggressiveness that animals present. Frequently, animals fight to establish a dominance hierarchy and obtain a disputed resource. The Mexican mojarra Cichlasoma istlanum is a native species of the Balsas river basin and coexists there with four nonnative cichlids: tilapia Oreochromis sp., convict cichlid Amatitlania nigrofasciata, spotcheek cichlid Thorichthys maculipinnis, and green terror Andinoacara rivulatus. These five cichlid species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 86 publications
0
3
0
2
Order By: Relevance
“…Though there was a reduction in aggressive behavior of catfish towards rohu fingerlings when compared to aggression shown towards conspecifics (in C and SC trials) or large-size rohu (in C/R trials). This was not surprising as rohu fingerling was a weak competitor (in terms of reduced feeding duration) in presence of catfish, and thus, received less aggression from the catfish (Franco and Arce, 2022). Interestingly, in C/R trials, both species of large-size classes showed comparable feeding durations, and displayed similar or even higher levels of aggression towards each other (Miyai et al 2011; McCarthy et al, 1999) when compared to the respective conspecific (C or R) trials.…”
Section: Discussionmentioning
confidence: 98%
“…Though there was a reduction in aggressive behavior of catfish towards rohu fingerlings when compared to aggression shown towards conspecifics (in C and SC trials) or large-size rohu (in C/R trials). This was not surprising as rohu fingerling was a weak competitor (in terms of reduced feeding duration) in presence of catfish, and thus, received less aggression from the catfish (Franco and Arce, 2022). Interestingly, in C/R trials, both species of large-size classes showed comparable feeding durations, and displayed similar or even higher levels of aggression towards each other (Miyai et al 2011; McCarthy et al, 1999) when compared to the respective conspecific (C or R) trials.…”
Section: Discussionmentioning
confidence: 98%
“…Our study demonstrates that individuals performing more bites relative to their opponents were the ones with the greatest probability of winning. In highly aggressive species like the Mexican mojarra (Franco & Arce, 2022) factors such as size may not be the only essential determinants in contest outcomes (Jang et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…En nuestros resultados, aunque A. nigrofasciata presentó abundancias elevadas con relación a otras especies, esta no fue mayor a la observada para el cíclido nativo. Adicionalmente, en combates experimentales se ha demostrado que A. istlanus es dominante frente a A. nigrofasciata, lo cual podría sugerir que la competencia por interferencia no explica el número de individuos observados en el Río (Archundia & Arce, 2019;Franco & Arce, 2022;Molina et al, 2021). Otros estudios han reportado que estas especies no presentan competencia por alimento al ser la nativa carnívora y la no nativa entomófago-omnívora.…”
Section: Discussionunclassified
“…Con ello se puede explicar que sea común encontrar baja abundancia y tallas menores de A. istlanus donde A. nigrofasciata es abundante y presenta tallas mayores, y viceversa. Nuestra investigación sugiere, al igual que otros trabajos (Archundia & Arce, 2019;Franco & Arce, 2022;Molina et al, 2021) que las poblaciones de la especie nativa no necesariamente están siendo reducidas, al haber áreas donde la especie nativa es dominante. Sin embargo, es importante mantener atención sobre las interacciones entre estas especies y los posibles efectos de la presión de la especie no nativa.…”
Section: Discussionunclassified